The Protective Effect of Omega-7 on Cisplatin-Induced Nephrotoxicity in Rat Model - Shurouqhussam; Ali Faris Hassan (Iraqi Journal of Pharmaceutical Sciences, 2023)
Omega-7 is a monounsaturated fatty acid that has a number of beneficial effects. Cisplatin, an effective antineoplastic agent is commonly used to treat solid tumors. Cisplatin΄s clinical use has been limited due to its nephrotoxicity. Nephrotoxicity induced by Cisplatin is thought to be linked with increased formation of reactive oxygen species. The purpose of this study was to evaluate the anti-oxidant effect of omega 7 against Cisplatin induced nephrotoxicity. thirty male wistar rats were divided randomly into five groups with six rats in each group , group 1 rats received liquid paraffin solution orally for 7 consecutive days , group 2 rats received single intraperitoneal injection of Cisplatin (7.5 mg/ kg) , group 3 rats received omega-7 (50mg/ kg) orally for 7 consecutive days and then received Cisplatin single intraperitoneal injection (7.5mg/ kg) on day 8 , group 4 rats received omega-7 (100 mg/ kg) orally for 7 consecutive days and then received single intraperitoneal injection of Cisplatin (7.5mg/ kg) on day 8 , group 5 rats received omega 7 (100mg/ kg) orally for 7 consecutive days .on the ninth , all animals were sacrificed and tissue homogenates were used for the estimation of glutathione peroxidase-1(GPX-1), superoxide dismutase-1(SOD-1), reduced glutathione(GSH), catalase(CAT) and malondialdehyde(MDA). Treatment of rats with omega-7 showed significant (p < 0.05) elevation in the activities of anti-oxidant enzymes (GPX-1, SOD-1, reduced GSH and CAT) and significant (p < 0.05) reduction of MDA level compared to Cisplatin (positive control) group.in conclusion, omega-7 has a protective effect against Cisplatin-induced nephrotoxicity maybe through its anti-oxidant activity.